2017
DOI: 10.1016/j.psychres.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

PTSD's risky behavior criterion: Relation with DSM-5 PTSD symptom clusters and psychopathology

Abstract: A new symptom criterion of reckless and self-destructive behaviors (E2) was recently added to posttraumatic stress disorder’s (PTSD) diagnostic criteria in DSM-5, which is unsurprising given the well-established relation between PTSD and risky behaviors. Researchers have questioned the significance and incremental validity of this symptom criterion within PTSD’s symptomatology. Unprecedented to our knowledge, we aim to compare trauma-exposed groups differing on their endorsement status of the risky behavior sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 89 publications
2
33
2
Order By: Relevance
“…irrelevant topic). Contractor, Weiss, Dranger, Ruggero, and Armour (2017) and Erwin et al (2018) reported data from the same study and we used the data reported in Erwin et al We were not able to review full texts of seven PhD dissertations and two articles in Polish journals (Bokszczanin, 2003;Bokszczanin & Kaniasty, 2002) as we were not able to retrieve the respective full texts. Another five journal articles failed to report the required data.…”
Section: Study Selectionmentioning
confidence: 99%
“…irrelevant topic). Contractor, Weiss, Dranger, Ruggero, and Armour (2017) and Erwin et al (2018) reported data from the same study and we used the data reported in Erwin et al We were not able to review full texts of seven PhD dissertations and two articles in Polish journals (Bokszczanin, 2003;Bokszczanin & Kaniasty, 2002) as we were not able to retrieve the respective full texts. Another five journal articles failed to report the required data.…”
Section: Study Selectionmentioning
confidence: 99%
“…This has important implications for clinical practice, in which patients who present with high elevations of specific PTSD symptomatology could be further assessed for their engagement in reckless behaviors, as the elimination or reduction of these behaviors could potentially contribute to reduced functional impairment as well as reduced chances of bodily harm to the self and others. Further, a detailed examination of reckless behaviors related to PTSD is important, as the engagement in these behaviors may be associated with more comorbidity (Contractor, Weiss, Dranger, et al., 2017), decreased effectiveness of PTSD interventions (Tarrier, Sommerfield, Pilgrim, & Faragher, 2000), and even threat to one's life through dangerous driving, substance overdose, and suicidal behaviors.…”
Section: Symptom Clusters In the Dsm‐5 Seven‐factor Hybrid Model (Armmentioning
confidence: 99%
“…Such reckless behaviors can arise, alongside other symptoms, in response to traumatic events (Green et al, 2005), and engagement in reckless behaviors can increase the risk an individual will experience subsequent traumatic events (Lusk, Sadeh, Wolf, & Miller, 2017). Research has supported the relation between reckless behaviors and PTSD diagnosis (Weiss, Tull, Viana, Anestis, & Gratz, 2012) as well as PTSD severity (Contractor, Weiss, Dranger, Ruggero, & Armour, 2017;Lusk et al, 2017;Pat-Horenczyk et al, 2007;Strom et al, 2012;Weiss, Tull, Borne, & Gratz, 2013). Different reckless behaviors serve different functions, which could explain their heterogeneous associations with PTSD symptom clusters.…”
mentioning
confidence: 99%
“…This study was approved by a Midwestern university's Institutional Review Board. The present study is a secondary analysis of this larger dataset (see Contractor et al 2017 for full study details).…”
Section: Procedures and Participantsmentioning
confidence: 99%
“…The present study is a secondary analysis of this larger dataset (see Contractor et al 2017 for full study details). Participants were recruited from waiting rooms at a Midwest community mental health center.…”
Section: Compliance With Ethical Standardsmentioning
confidence: 99%